2013
DOI: 10.18632/oncotarget.1122
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A2 is regulated by ovarian cancer-peritoneal cell interactions and promotes metastasis

Abstract: Our recent research identified the protein annexin A2 to be regulated by ovarian cancer-peritoneal cell interactions. This study investigated the role of annexin A2 in ovarian cancer metastasis and its potential utility as a novel therapeutic target, using in vitro and in vivo ovarian cancer models. Annexin A2 expression was examined by qRT-PCR and western blotting in ovarian cancer cell lines and immunohistochemistry in serous ovarian carcinoma tissues. Annexin A2 siRNAs were used to evaluate the effects of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
71
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 70 publications
(83 citation statements)
references
References 35 publications
8
71
0
4
Order By: Relevance
“…These in vitro observations concur with a recent study highlighting that acquired chemotherapy resistance in ovarian cancer patients is associated with 23:11 the increased expression of the ABC transporter, ABCB1 (Patch et al 2015). Importantly, we have demonstrated that serum HA levels are increased in ovarian cancer patients following chemotherapy and at recurrence, and can predict prognosis (Ricciardelli et al 2013). Reducing HA production is, therefore, a promising strategy to improve ovarian cancer survival in patients with chemoresistant disease and a focus of ongoing research.…”
Section: :11supporting
confidence: 91%
See 4 more Smart Citations
“…These in vitro observations concur with a recent study highlighting that acquired chemotherapy resistance in ovarian cancer patients is associated with 23:11 the increased expression of the ABC transporter, ABCB1 (Patch et al 2015). Importantly, we have demonstrated that serum HA levels are increased in ovarian cancer patients following chemotherapy and at recurrence, and can predict prognosis (Ricciardelli et al 2013). Reducing HA production is, therefore, a promising strategy to improve ovarian cancer survival in patients with chemoresistant disease and a focus of ongoing research.…”
Section: :11supporting
confidence: 91%
“…These studies have led to the identification of several proteins that are mechanistically involved in the peritoneal spread of ovarian cancer and may serve as novel ovarian cancer biomarkers and/or therapeutic targets. Studies with Ph.D. students Noor Lokman and Miranda Ween identified a key link between the annexin A2 signalling pathway and activation of the plasminogen-plasmin system (Ween et al 2011b, Lokman et al 2013, Ricciardelli et al 2015. Our findings, together with published literature, support the notion that ECM processing via the plasminogenplasmin pathway promotes the colonisation and attachment of ovarian cancer cells to the peritoneum and actively contributes to the early stages of ovarian cancer metastasis.…”
Section: :11supporting
confidence: 78%
See 3 more Smart Citations